Kolaborasi Antara Ekonomi Hijau dan Ekonomi Islam dalam Mencapai Kesejahteraan Sosial dan Lingkungan: Analisis Terhadap Strategi Pembangunan Berkelanjutan Society 5.0 - Permana, Ngadi; Eka Wahyu (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study aims to analyze the collaboration between green economy and Islamic economy in achieving social and environmental welfare through sustainable development strategies within the context of Society 5.0. The green economy, which emphasizes sustainable management of natural resources and environmental friendliness, can strengthen the principles of Islamic economy focused on social justice, environmental balance, and equitable wealth distribution. The integration of these two concepts is expected to create an inclusive and sustainable economic system that supports the achievement of Sustainable Development Goals (SDGs). However, its implementation requires policies that accommodate the social, cultural, and political conditions of each country. This study concludes that the collaboration between green economy and Islamic economy offers great potential for creating holistic social and environmental welfare in the Society 5.0 era